The relationship between syntax and semantic in the case of Ma`ani Nahwi in Arabic and the idea of Modistae in Latin - Yaacob, Solehah@Nik Najah Fadilah (David Publishing Company, 2010)
The research emphasizes on the relation of the Arabic concept of “ma`ani nahwi” and the Latin “modistae”. In order to establish this relation, the researcher illustrates the role of Aristotle’s categories in influencing the concept of the Medieval Latin “modistae”. This is followed by a reevaluation of the influence of Arabic philosophers, such as al-Farabi (c.870-c.950 CE), Avicenna (980-1037 CE) and Averoes (c.1126-c.1198 CE) on Latin philosophy and linguistics, especially Jurjani’s (d.1078 CE) role in introducing his concept of “nazm” towards “ma`ani nahwi”. The research contributes to the understanding of the relationship between syntax and semantics which has not been effectively clarified within the framework of traditional Arabic grammatical theory.